Ez printing / Ahmad Daniel Haiqal Zahid ...[et al.] - Zahid, Ahmad Daniel Haiqal; Mohd Suhardi, Muhammad Luqman; Rahman, Muhammad Hizami; Hamsah, Muhammad Hakimi (2023)
The objective of this business plan is to secure long-term funding in order to open a EZ Printing services shop. EZ Printing is a partnership business company located at Sungai Besi, Kuala Lumpur. EZ Printing is focused on a partnership consisting of four partnership member that invest the same amount of capital which is RM15,000 of each member and it will be total capital amounted for RM60,000. Moreover, the administration, operational, marketing and financial plan are all included in this business plan. Our business is in the industry of products and services. Our service is a design and printing on various types of fabric for t-shirt. Then, our main target customer is students, working people and family and those who want to print t-shirt with their design. For example, the company that have special events or program that needed identical design on t shirt, they can find us to give their solution. Furthermore, by bringing the high quality of the product, negotiation of the price and design and comfortable product and material that suit our environment and climate, our product and services will become preferable among our target market. Moreover, our company plans to build a strong market position in Sungai Besi and aims to offer the good qualities at a competitive price to meet the demand of the customer in area residents, working people, student and individual. Our products are designed to customize in fulfill the demand and preferences of our customers. Our company saw the opportunity that this business has the potential of success in this area and can be leading in market share of this industry. Finally, we expect that EZ Printing will blossom into a well-known national brand and will be able to provide additional services on occasion. We also expect that the demand for our products and printing services will rise year after year as the human population grows, allowing us to meet our business objectives with our business financial position statement.